Literary Experiment from C.E. Gadda to Neo-Avant-Garde: Continuity and Transformation - Anastasia V. Golubtsova (Studia Litterarum, 2020)
The article examines the influence of Carlo Emilio Gadda, one of the greatest Italian 20th century authors, on the Italian Neo-Avant-Garde of the 1960s, an experimental literary movement aimed at undermining the pillars of the established society (clichéd patterns, widespread beliefs, and myths) by destroying traditional language. In his novels The Experience of Pain and That Awful Mess on Via Merulana, Gadda invents his own peculiar “language,” a complex combination of various linguistic and cultural codes, intertextual references and quotations. Gadda’s texts fully published in the 1950s-1960s, in the period of animated discussions around Neo-Avant-Garde theory and practice, become aesthetic models for the young authors, especially for Luigi Malerba and Giorgio Manganelli. Gadda’s works influence Neo-Avant-Garde ideas, themes, and linguistic techniques, even though Gadda does not share Neo-Avant- Garde’s anti-ideological and destructive spirit. He mixes and transforms different codes seeking to reveal hidden connections between things, to reach back to the cultural tradition, and to convey reality in its fullness, while Neo-Avant-Garde perceives Gadda’s language as a means of social and cultural criticism that allows to discredit myths and ideologies, and denies any possible reconstructive meanings of literary experimentation.